If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7.2 + -3x = 2c + -2 Reorder the terms: 7.2 + -3x = -2 + 2c Solving 7.2 + -3x = -2 + 2c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7.2' to each side of the equation. 7.2 + -7.2 + -3x = -2 + -7.2 + 2c Combine like terms: 7.2 + -7.2 = 0.0 0.0 + -3x = -2 + -7.2 + 2c -3x = -2 + -7.2 + 2c Combine like terms: -2 + -7.2 = -9.2 -3x = -9.2 + 2c Divide each side by '-3'. x = 3.066666667 + -0.6666666667c Simplifying x = 3.066666667 + -0.6666666667c
| 2.5n=13 | | 35x^2-35x=0 | | 180-x+5=x-3+x-2 | | 0.7x=1.4-0.3x | | 9-(4z-7)=4-5z | | x^3-66x+118=0 | | -5=a-2 | | (5y-8)(4-y)=0 | | 2n^2+11n-45=2n^2 | | 7m=22 | | 0.75x+0.05(16-x)=0.10(78) | | r/4=6 | | 3/4(5x-8) | | 11=-7x-5(-2x+2) | | 22N^2+11N-45=-2n^2 | | 41.71+0.10x=110 | | 6(4t+2)=3(11t+11) | | 41.71+0.10=110 | | 9y-6=5y+2 | | 88=5x-3(3x-16) | | 7k+1=k | | x^2(x-5)=-6x | | 3x-45=x+15 | | (x-3)/(5)=2 | | 8=5w(w+4) | | X^2+4+11=0 | | s-14=96 | | s-14s=96 | | .8-2x=2.7 | | 2(x+6)=4(2x+1) | | 6.5(x-3)=2.4(3-8) | | y-13=-14+9y |